Bibliometric Analysis of the Influence of Fundamental Political Policies on Gold/USD Price Movements - Anthony Andrew Wahyu Kusumo Hadi (Faculty of Economics and Bussiness, Universitas Diponegoro, Semarang, Indonesia, 2025)
In the wake of rising geopolitical tensions and economic uncertainties, understanding how fundamental political policies influence gold and USD price dynamics is critical for investors and policymakers. This study aims to systematically map existing literature on the interplay between policy decisions and gold/USD movements using a qualitative bibliometric approach. The author retrieved 1,000 publications from Google Scholar (2020–2025), extracted publication metrics via Publish or Perish, and visualized co‑authorship and keyword co‑occurrence networks with VOSviewer. Four thematic clusters emerged: (1) digital finance and system scalability, (2) policy uncertainty and crisis impact, (3) market efficiency and political dynamics, and (4) emerging financial technologies. High‑relevance terms such as wavelet, pandemic, scalability, blockchain, and political risk underscore the dominance of advanced quantitative methods, crisis‑driven market analysis, infrastructural challenges, and policy‑induced volatility. Our findings highlight the importance of integrating economic, political, and technological dimensions to inform adaptive policy frameworks and stabilize markets. This bibliometric synthesis provides a foundation for future empirical research exploring policy‑driven gold and currency price behavior. This research makes an original contribution by applying a comprehensive bibliometric analysis to map the evolution of literature on fundamental political policies and gold/USD price dynamics, and by identifying underexplored research gaps.